Orientaciones ecológicas para la recuperación de áreas marginales de olivar - Ramírez L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Potential evapotranspiration, index of continentality, and frequency of frosts have been studied in relation to the distribution of olive trees in Spain. While index of continentality is not connected with olives groves, evapotranspiration and frosts seem to limit their distribution. An index of marginality of olive groves has been obtained on there two variables. Finally, proposed actions in order to improve the situation of less productive olive crops are discussed.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)